[Steam and hot water lines, Babicora Ranch, Chihuahua, Mexico] (1943)
Steam and hot water lines in old house at Babicora Ranch, Chihuahua. Boiler room in background. Photograph was included in a letter dated September 25, 1943, to Julia Morgan from Rafael Campos.